Acquiring reason. - Ionel, Lucian (European Journal of Philosophy, 2022)
In the last decades, there has been a far‐reaching debate about whether reason is a natural power of the human animal or a socio‐historical achievement. This paper brings out and criticizes two paradigmatic views of reason entangled in that dilemma: the substantive view which construes reason as a primitive power possessing the basic forms of intelligibility; and the derivative view which traces back reason to non‐rational, natural‐historic processes. I approach the issue by discussing how Aristotle addresses the underlying predicament in Metaphysics Theta. The predicament persuades us to overdetermine or underdetermine our natural potentiality for reason because it ignores what I call Aristotle's main insight: the understanding from which rational capacities are exercised is acquired by undertaking appropriate activities. The measure of rational capacities is neither merely naturally determined nor merely socio‐historically inherited but relies on the engagement with the things falling under the purview of the pertaining activities. We must recover this Aristotelian insight, I argue, to avoid succumbing to either the substantive or the derivative view of reason.